A global meta‐analysis reveals higher variation in breeding phenology in urban birds than in their non‐urban neighbours. (22nd September 2022) - Capilla‐Lasheras, Pablo; Thompson, Megan J.; Sánchez‐Tójar, Alfredo; Haddou, Yacob; Branston, Claire J.; Réale, Denis; Charmantier, Anne; Dominoni, Davide M.
Abstract: Cities pose a major ecological challenge for wildlife worldwide. Phenotypic variation, which can result from underlying genetic variation or plasticity, is an important metric to understand eco‐evolutionary responses to environmental change. Recent work suggests that urban populations might have higher levels of phenotypic variation than non‐urban counterparts. This prediction, however, has never been tested across species nor over a broad geographical range. Here, we conducted a meta‐analysis of the avian literature to compare urban versus non‐urban means and variation in phenology (i.e. lay date) and reproductive effort (i.e. clutch size, number of fledglings). First, we show that urban populations reproduce earlier and have smaller broods than non‐urban conspecifics. Second, we show that urban populations have higher phenotypic variation in laying date than non‐urban populations. This result arises from differences between populations within breeding seasons, conceivably due to higher landscape heterogeneity in urban habitats. These findings reveal a novel effect of urbanisation on animal life histories with potential implications for species adaptation to urban environments (which will require further investigation). The higher variation in phenology in birds subjected to urban disturbance could result from plastic responses to a heterogeneous environment, or from higher genetic variation in phenology, possibly linked to higher evolutionary potential. Abstract : Phenotypic variation is an important metric to understand eco‐evolutionary responses to environmental change. We conduct a meta‐analysis of the bird literature to compare urban versus non‐urban means and variation in phenology and reproductive effort. We show that urban populations reproduce earlier, have smaller broods and have higher phenotypic variation in laying date than non‐urban conspecifics.